RESPON TANAMAN SAWI (Brasicca juncea L.) TERHADAP PEMBERIAN PUPUK ORGANIK CAIR (POC) KULIT PISANG DAN BONGGOL PISANG - Yusran Ibrahim; Ramlin Tanaiyo (Fakultas Pertanian Universitas Ichsan Gorontalo, 2018)
The aimed of this research was to know the effect of giving the liquid organic fertilizer from peel and hump of banana on mustard plant (Brasicca juncea L.) into the mustard crop. The research was conducted in March - April 2016, in Toto Utara Village, Tilongkabila District, Bone Bolango Regency. The study was prepared using randomized block design (RAK), which consisted of three treatments and three replications, so there were 9 (nine) experimental plots using polybag planting media. Different dose on 2 (two) treatments that was without treatment P0 (control), concentration of 100 ml / liter of water banana peel liquid organic fertilizer 20 ml/ plant + banana hump liquid fertilizer 20 ml/ plant (P1), and concentration 100 ml/ liter water banana peel liquid organic fertilizer 40 ml/ liquid organic fertilizer from banana hump 40 ml/plant (P2). Fertilization carried out at the time of mustard plants were 3 HST and 9 HST. Based on the results of research after the analysis statistically showed that treatment with liquid organic fertilizer from banana peel and banana hump did not give a real effect on all observation parameters.